2006
DOI: 10.1196/annals.1326.021
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐Like Receptor Expression and Response to Specific Stimulation in Adipocytes and Preadipocytes

Abstract: Data in this study indicate that both adipocytes and preadipocytes express abroad set of TLRs and they also respond to specific stimulation by cytokine production. The may be of relevance to Crohn's disease and a suggests a closer link between adipose tissue and innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 4 publications
2
51
0
1
Order By: Relevance
“…This is also the case in ob/ob mice lacking leptin, with the exception that TLR7 is not expressed in mature adipocytes. Murine wild-type adipocytes (derived from C57Bl/6 or 3T3-F442A mice) do not express TLR7 and TLR8, whereas the respective preadipocytes express TLR7 mRNA [5,19]. Batra et al demonstrated a significant upregulation of TLR1-TLR9 mRNA expression in pre-adipocytes derived from ob/ob and db/db mice (compared with wild-type mice [20]), in which TLR responsiveness increased during differentiation.…”
Section: Does Adipose Tissue Express a Broad Spectrum Of Tlrs?mentioning
confidence: 95%
See 1 more Smart Citation
“…This is also the case in ob/ob mice lacking leptin, with the exception that TLR7 is not expressed in mature adipocytes. Murine wild-type adipocytes (derived from C57Bl/6 or 3T3-F442A mice) do not express TLR7 and TLR8, whereas the respective preadipocytes express TLR7 mRNA [5,19]. Batra et al demonstrated a significant upregulation of TLR1-TLR9 mRNA expression in pre-adipocytes derived from ob/ob and db/db mice (compared with wild-type mice [20]), in which TLR responsiveness increased during differentiation.…”
Section: Does Adipose Tissue Express a Broad Spectrum Of Tlrs?mentioning
confidence: 95%
“…Scherer and colleagues demonstrated that a member of the TLR family, TLR2, is expressed in 3T3-L1 adipocytes, and is induced by the TLR4 ligand, LPS [4], which suggests that there is an adipose-tissue-based TLR signaling pathway. The pattern of TLR expression [18,19] in adipocytes (for summary, see Ref. [5]) is highly dependent on the state of differentiation (pre-adipocytes versus mature adipocytes), on the species (human versus murine), on the cell type (cell lines versus primary cells), and on the presence or absence of genetically induced obesity (e.g.…”
Section: Does Adipose Tissue Express a Broad Spectrum Of Tlrs?mentioning
confidence: 99%
“…Additionally, more and more in vitro experiments show that mature adipocytes and preadipocytes express a wide variety of functional toll-like receptors (TLRs) that respond to specific stimuli by producing cytokines, such as IL-6 [52,53]. Furthermore, as inflammatory stimuli, TNF-a and IL-6 itself also promote IL-6 production in vitro [54].…”
Section: Effects Of Inflammationmentioning
confidence: 99%
“…Multiple TLRs (TLR1-5, 7, and 9) are expressed on adipocytes, at least some of which appear to be functionally active [107][108][109][110]. High levels of free fatty acids from obesity and glucose from diabetes activate the innate immune system, with upregulated TLR expression that correlates with insulin resistance and increased inflammatory cytokine release in macrophages [111][112][113].…”
Section: Mechanism Of Association Between Ad and Metabolic Factorsmentioning
confidence: 99%